Maintenance of Office Facilities at the Makassar City Public Works Service - Haedar Akib; Nur Rini Abdullah; Risma Niswaty; Sitti Hardiyanti Arhas; M. Awaluddin (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Maintenance is the activity to maintain equipment so that the activation process can run smoothly to get the results as planned. One of the needs to support the smooth productivity and competitiveness of the office is the availability of office facilities that can support the success of the office to meet shared needs. The purpose of this study was to find out how to maintain office facilities at the Makassar City Public Works Department. To determine the purpose of the study, qualitative descriptive research was used. There were 7 informants in this study using data collection techniques through observation, interviews, and documentation. The data obtained from the research results are then processed using data analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The results showed that the maintenance of office facilities at the Makassar city public works service was routine, periodic, emergency, and prevention is good enough. Thus it can be concluded that the maintenance of office facilities at the Makassar City Public Works Department has been carried out properly.